Combination of Total Psoas Index and Albumin–Globulin Score for the Prognosis Prediction of Bladder Cancer Patients After Radical Cystectomy: A Population-Based Study - Wang, Keyi; Gu, Yongzhe; Ni, Jinliang; Zhang, Houliang; Xie, Jinbo; Xu, Tianyuan; Geng, Jiang; Mao, Weipu; Peng, Bo (Frontiers in Oncology, 2021)
Backgrounds: Sarcopenia as the loss of skeletal muscle mass, is related with poor postoperative survival. This work purposed to evaluate the prognostic prediction of total psoas index (TPI), albumin-globulin score (AGS) and the combination of TPI and AGS (CTA) in bladder cancer (BCa) patients after radical cystectomy. Methods: BCa patients received radical cystectomy between 2012 and 2020 were retrieved from our medical center. The calculation of TPI was based on the plain computed tomography images. The predictive effect of TPI, AGS and CTA grade on survival of BCa patients were analyzed and compared with albumin-globulin ration (AGR) through the receiver operating characteristic (ROC) curves. A nanogram was further established based on the cox regression results from CTA grade and clinicopathological characteristics, which verified by decision curve analysis (DCA) Results: A total of 112 eligible patients diagnosed as BCa were included in this study for retrospectively analyzation. The patients with lower TPI or higher AGS grade (1/2) contained the poorer overall survival (OS) and disease-free survival (DFS). Divided by CTA grade, there were 35 (31.25%) patients in grade 1 associated with the best postoperative prognosis, which accompanied with increased TPI and decreased AGS. The CTA grade could better predict postoperative outcomes compared with TPI, AGR and AGS for the highest area under curve (AUC; 0.674 of OS and 0.681 of DFS). The 3- and 5-year OS and DFS nanograms were conducted based on CTA grade and clinical variables, with the higher predictive performance than TNM-stage. Conclusion: This study revealed the novel index CTA functioned as the effective prognostic predictor for postoperative OS and DFS of BCa patients after radical cystectomy. Preoperative assessment of CTA would contribute to optimizing clinical therapies.